The Clash of Traditional and Modern Cultures in the Novels Samdae (Three Generations) by Yeom Sang Seop and Tetralogi Buru (Buru Quartet) by Pramoedya Ananta Toer - Febriani Elfida Trihtarani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This study analyzes Korean writer Yeom Sang-seop's colonial-era novel Samdae (Three Generations) (1931) and Pramoedya Ananta Toer's Tetralogi Buru (Buru Quartet). Although Korea and Indonesia have different cultures, they share a history of colonization by imperial countries. The purpose of this study is to analyze the writers' cultural differences as they appear in these novels. Yeom Sang-seop’s Samdae (Three Generations) is shown to capture the conflict of traditional and modern cultures. In this novel, characters who follow traditional culture consider customs and honor very important. Meanwhile, the characters in Pramoedya’s quartet consider honor to be important. In Yeom Sang-seop’s novel, those seeking modernity hold only modern ideas and ultimately fall victim to consumerism. On the other hand, in Pramoedya’s novels, while characters with modern ideas do exist, they are not trapped in a world of consumerism. Yeom Sang-seop seeks a solution to escape colonialism through one character who is not interested in traditional culture but also shows no significant interest in modern culture. He instead supports socialism, which can be considered an attempt to avoid the downsides of modernity. In the novels of Pramoedya, one character Minke faces a similar situation. Through his national organizing activities, he shows the possibility that Indonesia can break free of colonialism.